BIMBINGAN TEKNIS PERHITUNGAN PERSEDIAAN PADA UMKM TOKO KURNIA BANJARMASIN - Sirajudin; Mukhlisah, Nurul; Farida, Lea Emilia (Jurnal IMPACT: Implementation and Action, 2022)
Toko Kurnia Banjarmasin is an SME that has just started their business in the midst of the COVID-19 pandemic which has limited skills in calculating and recording their inventory. A business is considered ideal if the existing inventory has served in sufficient to customer demand or for production purposes. An information about inventory availability can be seen in the inventory ledger that obtained through inventory calculations. Those problems occurred especially for the SME owner of Toko Kurnia Banjarmasin, therefore this community service activity is held to provide a solution in the form of technical guidance on calculating and recording merchandise inventory. This activity aims to provide knowledge and skills to calculate and record inventory of merchandise so that they can monitor the existing inventory. Inventory control will be able to determine the level of cost efficiency in inventory and its effect on profit and loss. The method of community service is provided in technical guidance on calculating and recording inventory as well as exercises/practices using simple working papers. This activity was successfully carried out on Saturday, August 14, 2021, attended by the owner of the Banjarmasin Kurnia Shop, the head of the Poliban Accounting Department and Study Program and the service committee. The activity ran smoothly where participants were given an introduction to supplies and inventory characters first. Then, an explanation of the various inventory recording methods commonly used in accounting was given along with an example of each calculation. After that, we continued with the inventory calculation exercise with examples of the types of goods available at the Banjarmasin Kurnia Store.